2010
DOI: 10.1364/ao.50.000116
|View full text |Cite
|
Sign up to set email alerts
|

Structure, growth, and optical properties of TbAl_3(BO_3)_4 single crystal

Abstract: TbAl(3)(BO(3))(4) single crystal was grown from a K(2)Mo(3)O(10)-B(2)O(3) system using the top-seeded high temperature solution method (TSSG), 20 mm×9 mm×7 mm in size. The grown crystal was characterized by x-ray diffraction analysis showing that the crystal has a trigonal structure and the space group is R32 with lattice parameters of a = b = 9.293(13) Å, c = 7.249(6) Å. Faraday rotations of TbAl(3)(BO(3))(4) crystal were investigated at room temperature at wavelengths of 532, 633, and 1064 nm. Finally, the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The cell parameters are a ¼ b ¼ 9:2933 Å and c ¼ 7:2496 Å . 34 The O-B-O bond angle is 120 and the B-O bond distance is 1.383 Å . In the FP-LAPW method, the unit cell is divided into two parts: non-overlapping atomic spheres centered at the atomic sites and the interstitial region.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cell parameters are a ¼ b ¼ 9:2933 Å and c ¼ 7:2496 Å . 34 The O-B-O bond angle is 120 and the B-O bond distance is 1.383 Å . In the FP-LAPW method, the unit cell is divided into two parts: non-overlapping atomic spheres centered at the atomic sites and the interstitial region.…”
Section: Methodsmentioning
confidence: 99%
“…A lot of experimental studies on the spectroscopic and optical properties of these materials have been performed, while a theoretical treatment is lacking in the literature. [23][24][25][26][27][28][29][30][31][32][33][34][35] Recently, Chaudhury et al 23 have studied the magneto-electricity and magneto-striction in TmAl 3 (BO 3 ) 4 and concluded that the magneto-electricity is related to the piezoelectric effect of the non-centrosymmetric structure. The giant magnetoelectric effect in HoAl 3 (BO 3 ) 4 has been found to increase with decreasing magnetic anisotropy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition it provides the simplest model to track the temperature dependence. [43]. Atomic displacement parameters are anisotropic (U 11 = U 22 ≠ U 33 ) due to the hexagonal nature of the cell.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…Moreover, the reported TbCOB crystal exhibited an additional absorption band in the visible, which hampered the spectroscopic measurements and limited its application in this spectral region. As a matter of fact, such color centers have already been observed in Tb 3+ -based crystals, e.g., TbAl 3 (BO 3 ) 4 , KTb­(WO 4 ) 2 , NaTb­(MoO 4 ) 2 , and Na 2 Tb 4 (MoO 4 ) 7 , and have not been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%